Optimization of Hot Pressing Process for Unidirectional Kenaf Polypropylene Composites by Full Factorial Design / Dulina Tholibon...[et al.] - Tholibon, Dulina; Sulong, Abu Bakar; Muhamad, Norhamidi; Ismail, Nur Farhani (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
In recent years, the use of kenaf fibers as a reinforcement agent in the composite preparation has grown rapidly due to increasing requirement for developing sustainable materials. In this research, unidirectional kenaf polypropylene (PP) composites were prepared using the hot pressing method. However, there has been insufficient research in fabricating the unidirectional kenaf/PP composites that focus on optimum parameter's settings for hot pressing process. Therefore, a study of the optimization process emphasizing on temperature, pressure, time and percentage of kenaf fibers on the tensile properties was conducted with a two-level full factorial design. In addition, the effects of the individual factors and their interaction were also observed. The result showed that the main factor that affects the high-performance of tensile strength, and modulus were due to the kenaf percentage with 21.67% contribution. While, the interaction of kenaf percentage and pressing time influenced 13.26% contribution on the composite properties. Concluding that at temperature 190°C, pressure 5MPa, with 5 minutes pressing time and 50% fiber content will enable optimum tensile strength and young modulus which is 163.12 MPa and 11.17 GPa respectively. Therefore, this also ensures an improvement of 486% tensile strength compared to pure PP.